Transition amplitude for free massless particle - Zima, V.G.; Fedoruk, S.A. (Вопросы атомной науки и техники, 2001)
The propagator for massless particle of arbitrary spin is represented as BFV-BRST path integral in index spinor formalism. The classical formulation of the theory is investigated and it is carried out its Hamiltonization procedure. The structure functions are obtained. The BRST-charge of the model is calculated and it is shown, that it has the first rank. The expression for transition amplitude is transformed to the form of amplitude for a system with only the first class constraints. It is shown, that complexification of some phase variable results in the Gupta-Bleuler formalism. In these frameworks it is considered quantization procedure.